FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR (Students' Journal of Accounting and Banking, 2013)
This study main to find out and to analize the influence between the asset structure, sales growth, profitability and liquidity to capital structure of manufacture in Indonesia Stock Exchange. This study also reviews the variables that are used because there are differences in the results of previous researches. The research was conducted in BEI period 2008-2011 with purposive sampling method is the sampling method based on certain criteria. The amount of sample are 76 manufacture company in Indonesian Stock Exchange. This study analyzed using multiple regressions. The results of the study shows that asset structure variable, sales growth and profitability influences positive to the capital structure, while liquidity didn’t influence to the capital structure. Keywords: Capital structure, firm characteristics